"Fake news, " misinformation, and political bias: Teaching news literacy in the 21st century. Issue 2 (2nd April 2020) - Bonnet, Jennifer L.; Rosenbaum, Judith E.
ABSTRACT: In an era where claims of "fake news" abound and more people turn to social media for their daily updates, knowing how to find and critically appraise information is more important than ever. The workshop discussed in this article aims to provide college students with the news literacy needed to make educated decisions about the information they find online. Courses: This workshop is relevant for courses that address the evaluation of information, the value of different sources, the role played by personal biases, and the provenance of ideas, including Introduction to Communication, Public Speaking, Persuasive Communication, Health Communication, and Media Studies. Objectives: This activity aims to help students compare and contrast the different meanings of "fake news" and misinformation; identify the various biases that impact selection and interpretation of information; develop a set of guidelines with which to evaluate information quality; and apply evaluation guidelines to contemporary news items.